THE ROLE OF THE GOVERNMENT IN PROVIDING LEGAL PROTECTION TO WORKERS THAT WAS LAID OFF DUE TO THE COVID-19 PANDEMIC - Mahmuda Pancawisma Febriharini; Benny Bambang Irawan; Krismiyarsi Krismiyarsi (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2022)
This study aims to determine the role of the government in providing legal protection to workers who have been laid off due to the COVID-19 pandemic. The impact of Covid 19 has shaken the Indonesian economy and of course the biggest impact is felt in industrial relations, both macro and micro. Many companies are threatened with the continuity of their production, which has an impact on the survival of our workers. Many have been laid off with wages not paid in full. To support the welfare and continuity of work for workers as well as to support workers who have been laid off due to Covid-19, the Government has issued variousincentives for employers and workers, namely in the form of cash assistance in the form of Wage Subsidy Assistance (BSU) and issuing pre-employment cards thataims to provide training, namely to provide skills that can be used for industrial and entrepreneurship needs.